1980
DOI: 10.1139/v80-391
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics and mechanism of acid catalysed hydrolysis of lactams

Abstract: This paper is dedicated to Prof. Raymond U . Lemieux on the occasion of his 60th birthday PETER WAN, TOMASZ A. KEITH YATES. Can. J. Chem. 58,2423 (1980). The acid-catalysed hydrolysis of lactams of ring size 4-7, and of N-ethylacetamide, has been studied at various temperatures in 0-70% aqueous sulfuric acids. The kinetics have been analysed by means of the r-hydration parameter treatment and the transition-state activity coefficient (TSAC) approach. Except for the (3-lactam, all substrates show a strongpos~t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 8 publications
6
19
0
Order By: Relevance
“…By far the best combination of mechanisms, for compounds 2-6 and 9-12, was found to be an A-2 reaction with 3 H 2 0 in the dilute acid region and another A-2 process, this time using only one H 2 0 , in the more concentrated region, as suggested by the r-plots and in full agreement with the previous proposal for lactam hydrolysis (33). These mechanisms also fitted the experimental data well for benzamide, 1, except in the highly concentrated acid region; it was found that inclusion of a third mechanism, involving one bisulfate ion, produced an excellent fit in this case.…”
Section: Methodssupporting
confidence: 88%
See 4 more Smart Citations
“…By far the best combination of mechanisms, for compounds 2-6 and 9-12, was found to be an A-2 reaction with 3 H 2 0 in the dilute acid region and another A-2 process, this time using only one H 2 0 , in the more concentrated region, as suggested by the r-plots and in full agreement with the previous proposal for lactam hydrolysis (33). These mechanisms also fitted the experimental data well for benzamide, 1, except in the highly concentrated acid region; it was found that inclusion of a third mechanism, involving one bisulfate ion, produced an excellent fit in this case.…”
Section: Methodssupporting
confidence: 88%
“…Data for 9-10, and 11 in the 5-60% and 65-97°C ranges were taken from Wan el al. (33), as were data for 8 between 5% and 46% H,S04 at 33'C and for 12 between 5% and 6Wo at 25°C. The hydrolysis reaction products are detailed in the references cited.…”
Section: Methodssupporting
confidence: 58%
See 3 more Smart Citations